FROM A DISTANCE: A PHENOMENOLOGICAL STUDY OF THE LIVED EXPERIENCE OF TELECOMMUTERS WORKING REMOTELY IN VIRTUAL TEAMS - Damien C Michaud (Adult Education Research Conference, 2018)
In this paper, the social and emotional experience of telecommuters working remotely in interdependent virtual teams is explored through a phenomenological inquiry into participants' lived experiences.
Keywords: Telecommuting; Virtual Teams; Workplace Learning